PENGARUH GOOD CORPORATYE GOVERNANCE, INTELLECTUAL CAPITAL, DAN FIRM SIZE TERHADAP KINERJA KEUANGAN : STUDI KASUS PADA PERUSAHAAN SEKTOR CONSUMER NON-CYCLICAL SUB SEKTOR FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Huwaida, Luluk Khansa; Zahro, Nafi’ Inayati; Mulyani, Ulva Rizky (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
This research intends to test whether there is an influence of good corporate governance, intellectual capital, and firm size on financial performance. The population in this research are food & beverage companies listed on the Indonesia Stock Exchange from 2018 to 2022. In this research there were 77 samples. The sampling technique uses a purposive sampling method. The research method used is quantitative with data sources using data in the form of secondary data. Data analysis method is multiple linear analysis using SPSS version 27. The results of this research provide empirical evidence that partially the variables independent board of commissioners, institutional ownership, intellectual capital, firm size have no effect on financial performance, and managerial ownership has an effect on financial performance.